Mental health literacy and associated factors among traditional healers of Jimma town, southwest, Ethiopia 2020: a community based, cross-sectional study - Mideksa, Gudeta; Tesfaye, Elias; Yitayih, Yimenu; Sime, Yohanes; Aliye, Kemal; Gizaw, Abraham Tamirat (Frontiers in Psychiatry, 2024)
Background Traditional healers are in the front line to give the mental healthcare service in developing countries like Ethiopia. In Ethiopia, different studies were done focusing on the role of traditional medicine and perception of the community toward traditional medicine. However, there is paucity of studies, which shows the level of mental health literacy among traditional healers. Therefore, this study intended to mental health literacy level of traditional healers in Jimma town, Ethiopia. Method A community-based cross-sectional study design was employed among 310 participants. To select the participants from Jimma town, a stratified random sampling method was utilized from August 1 to September 30, 2020. The Mental Health Literacy Questionnaire was used to assess mental health literacy for assessment of mental health literacy among traditional healers. The collected data were coded and entered into EpiData version 4.6 and exported to SPSS version 25.0 for analysis. Bivariate and multivariable linear regression was used for data analysis. Result The finding of this study showed that the samples of traditional healers found in Jimma town scored a total mean of 95.91 ± 3.0025 for mental health literacy. Age [β = −0.052 (95% CI: −0.078, −0.026)], year of experience [β = 0.095 (95% CI: 0.067, 0.123)], family history of mental illness [β = 1.709 (95% CI: 0.543, 2.360)], history of professional help seeking on mental illness [β = 0.501 (95% CI: 0.715, 2.288)], history of getting information of mental illness on media [β = 0.941 (95% CI: 0.345, 1.538)], training on mental health [β = 2.213 (995% CI: 1.520, 2.906)], history of treating mental illness [β = 1.676 (95% CI: 0.808, 2.544)], and informal education [β = −1.664 (95% CI: −2.081, −1.247)] were factors significantly associated with MHL. Conclusion The mental health literacy of traditional healers mean score is lower than the mean score of other studies. Age, year of experience, training on mental illness, family history, history of professional help seeking, history of treating mental illness, information on mental illness, and informal education are significantly associated with mental health literacy. Therefore, structured training is very important to improve their level of mental health literacy.